Morpho-phylogenetic evidence reveals Pseudobionectria phoenicis gen. et sp. nov. (Bionectriaceae) from a mangrove habitat - Zhang, Sheng-Nan; Hyde, Kevin D.; Liu, Jian-Kui (Phytotaxa, 2024)
A bionectriaceous ascomycete was collected from palm rachides in a mangrove habitat. Multi-gene phylogenetic analyses indicated this fungus belongs within the Bionectriaceae, forming a sister lineage to Septofusidium herbarum and distinct from other known genera. In this study, we proposed the new genus Pseudobionectria to accommodate the novel species P. phoenicis. Pseudobionectria is distinguished from other genera in Bionectriaceae by its superficial, globose, brownish-orange ascomata with a black crown that is flattened on the top and hyphal appendages that merge with the subiculum below. The asci are unitunicate, lacking a visible apical ring, and the ascospores are 1-septate, oblong-ellipsoidal to fusiform, hyaline, and exhibit spinose ornamentation. The establishment of this new genus is supported by morphological and phylogenetic evidence. Additionally, this paper provides a synopsis of the genera within Bionectriaceae, including information on the type species, morphological characteristics, lifestyles, molecular data and key publications.